The Angiotensin Converting Enzyme Gene I/D Polymorphism in Polish Rowers - Zbigniew Jastrzębski; Marek Kolbowicz; Agata Leońska-Duniec; Tomasz Tomiak (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
Angiotensin converting enzyme gene (ACE) is the most frequently investigated genetic marker in the context of genetic conditioning of athletic predispositions. The product of the gene is a key component of the renin-angiotensin system (RAS) and the kallikrein-kinin system (KKS), mainly responsible for the regulation of blood pressure. The main aim of the study was to determine the possible interaction between the ACE I/D polymorphism and endurance athlete status in a group of Polish rowers in comparison with sedentary individuals. 121 male Polish rowers, members of academic sports clubs, and 115 unrelated volunteers, were recruited for the study. The PCR amplification of the insertion (I) or deletion (D) fragment of the ACE gene was performed. Compared with control group, the frequency of the I allele differ significantly from that found in rowers (57.4% vs. 44.3%; P=0.013) and the ACE genotype frequency amongst the whole cohort of rowers (30.6% II, 53.7% ID, 15.7% DD) was also different from expected values (control group 19.1% II, 50.4% ID, 30.4% DD; P=0.017). Our investigation confirms a positive association of the I allele of the ACE gene with endurance athlete status in a group of Polish rowers